THE LEGAL INSTRUMENTS OF PROTECTION OF ENVIRONMENT IN A SPA COMMUNE IN POLAND - Woźniak, Marta Róża (Review of European and Comparative Law, 2019)
Abstract: The author has undertaken to classify the legal instruments of environmental protection of in a health resort municipality (a spa commune) in Poland, regarding the aspect of their impacting the state of protection of natural environment. A spa commune has at its disposal a catalogue of its own tasks, which is complemented by those connected with maintaining medicinal functions of the spa and with meeting the requirements of the environment. The analysis of the content of regulations of law on environmental protection allows concluding that in relation to spas there are no – in principle – separate legal norms which regulate questions connected with protection of environment. While identifying the legal instruments of environmental protection, it was necessary to take into account a few normative areas, on the basis of which the following groups of instruments were distinguished: regulatory and “police” type, planning, control and financial. In the study, some selected legal and comparative aspects were also taken into consideration.